Left ventricular thrombus associated with arteriovenous extra corporeal membrane oxygenation - Makdisi, George; Hashmi, Zubair A.; Wozniak, Thomas C.; Wang, I-wen (Journal of Thoracic Disease; Vol 7, No 11 (November 28, 2015): Journal of Thoracic Disease, 2015)
Extra corporeal membrane oxygenation (ECMO) has remarkably progressed over the recent years. It has become an invaluable tool in the care of adults and pediatric patients with severe cardiogenic shock. At the initiation of ECMO support, the left ventricular contractility is profoundly impaired. Inadequate right ventricular drainage and bronchial circulation can lead to left ventricular distension, with potential deleterious consequences, ranging from inadequate myocardial rest, pulmonary edema, or intracardiac clot formation. Therefore, it is of extreme importance to ensure an adequate left ventricular drainage. Here we present a case of LV thrombus developed while the patient is on central venoarterial (VA) ECMO.